Sustainability Assessment of Agribusiness Clusters: A Case Study Based on Regional Sustainability Assessment Methodology - Sergiy Smetana; Christine Tamaśy; Alexander Mathys; Volker Heinz (German Journal of Agricultural Economics (GJAE), 2017)
Socioeconomic and environmental sustainability is becoming critical for the evaluation of regional development. Regional planning and policy development depend on accurate sustainability assessment for the estimation of genesis and evolution of agribusiness clusters. The lack of a universal methodology creates challenges for the analysis of regional issues and the role of separate industries in the sustainability of regional development. This research suggests and reviews the application of Regional Sustainability Assessment Methodology (RSAM) by using a case study approach with a special attention to agribusiness clusters. The empirical analyses reveal the importance of resource cycling in the regions, their dependency on external resources and self-sufficiency as indicators of regional sustainability (social, economic and environmental resource use efficiency) in a dynamic perspective, applicable to diverse regions and separate aspects of sustainability. The study areas include three sub-national level regions in Germany: two forming an agribusiness cluster, specialized in livestock-meat production (Vechta Landkreis and Cloppenburg Landkreis) and one control region (Hochsauerlandkreis). The application of RSAM revealed varying rates of resource use efficiency, self-sufficiency and dependency on external resources for both static and dynamic perspectives. The assessment indicated the potential of RSAM application for the static and dynamic assessment of regions with agribusiness clusters. At the same time, static analysis of separate aspects of sustainability (economic, social and environmental) was not informative. RSAM application to the separate types of resource analysis allowed identification of sustainability hotspots (unbalanced development, "weak sustainability" and increased dependency on separate resources).
Keywords: 330